Russia in the European context, 1789-1914 : a member of the family - McCaffray, Susan Purves; Melancon, Michael S., 1940- (Palgrave Macmillan, 2005)
This volume surveys nineteenth century Russian society and economy and finds that Russian institutions, practices and ideas fit the general European pattern for that period of rapid change. In the nineteenth century there were still many different ways to be European, and excessive generalization obscures the great diversity that still characterized European civilization. Moreover, these essays bring to light several points at which Russian legislation and thinking provided models for others to follow. The authors focus on key elements of how Russians envisaged and constructed their economy and society. This is an important contribution that increases understanding of Russian history at a time when Russia's relationship with the "West" is again debated.